To solve the system of equations using the elimination method, we start with the two equations:
- \( y = x^2 + 10 \)
- \( y = -7x - 2 \)
We can set these two equations equal to each other since they both equal \( y \):
\[ x^2 + 10 = -7x - 2 \]
Next, we will rearrange this equation to bring all terms to one side:
\[ x^2 + 7x + 10 + 2 = 0 \]
\[ x^2 + 7x + 12 = 0 \]
Now we will factor the quadratic equation:
\[ (x + 3)(x + 4) = 0 \]
Set each factor equal to zero:
- \( x + 3 = 0 \) → \( x = -3 \)
- \( x + 4 = 0 \) → \( x = -4 \)
Now we will find the corresponding \( y \) values for each \( x \) value by substituting back into either of the original equations. We will use the second equation \( y = -7x - 2 \).
-
For \( x = -3 \): \[ y = -7(-3) - 2 = 21 - 2 = 19 \] This gives the point (-3, 19).
-
For \( x = -4 \): \[ y = -7(-4) - 2 = 28 - 2 = 26 \] This gives the point (-4, 26).
Thus, the solutions to the system are:
- \((-3, 19)\)
- \((-4, 26)\)
So the answer is:
\((-3, 19)\) and \((-4, 26)\).